The - edited by Gilbert Meilaender and William Werpehowski (Oxford University Press, 2005)
The Oxford Handbooks series is a major new initiative in academic publishing. Each volume offers an authoritative and up-to-date survey of original research in a particular subject area. Specially commissioned essays from leading figures in the discipline give critical examinations of the progress and direction of debates